2023
DOI: 10.1111/jcpe.13842
|View full text |Cite
|
Sign up to set email alerts
|

The tree shrew as a new animal model for the study of periodontitis

Abstract: Aim: Periodontitis is an inflammatory, infectious disease of polymicrobial origin that can damage tooth-supporting bone and tissue. Tree shrews, evolutionarily closer to humans than commonly used rodent models, have been increasingly used as biomedical models. However, a tree shrew periodontitis model has not yet been established.Materials and Methods: Periodontitis was induced in male tree shrews/Sprague-Dawley rats by nylon thread ligature placement around the lower first molars. Thereafter, morphometric and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…gingivalis played in alveolar bone resorption. Studies showed that periodontitis models with different degrees of inflammation were constructed with different times of bacteria inoculation, ranging from 4 weeks to 10 weeks. In this experiment, 4 weeks and 10 weeks were adopted to simulate early and advanced periodontitis, and the expression of EphrinB2 and EphB4 was observed.…”
Section: Discussionmentioning
confidence: 99%
“…gingivalis played in alveolar bone resorption. Studies showed that periodontitis models with different degrees of inflammation were constructed with different times of bacteria inoculation, ranging from 4 weeks to 10 weeks. In this experiment, 4 weeks and 10 weeks were adopted to simulate early and advanced periodontitis, and the expression of EphrinB2 and EphB4 was observed.…”
Section: Discussionmentioning
confidence: 99%